Beginning C# 7 Programming with Visual Studio 2017 - Perkins, Benjamin; Hammer, Jacob Vibe; Reid, Jon D. (John Wiley and Sons, Inc. : Wrox, 2018)
Written in a friendly, mentor-style fashion, with each chapter building on previous ones, this book is full of helpful hints, tips, exercises, and full-fledged example code, and will teach you about all aspects of C# programming quickly and easily. --